Effect of a ribbed surface on the water transfer characteristics of a porous plate. (December 2018) - Zhao, Yulong; Yue, Like; Wang, Shixue; Li, Linjun; Wang, Fei
Highlights: Porous plates are commonly used in proton exchange membrane fuel cells. Porous plates are used to transfer water between two gases. The benefit of a porous plate with a ribbed surface was compared to a smooth plate. The ribbed porous plate improved the transfer of water between the two gases. The transfer ability was even better when the ribbed side faced the humidified gas. Abstract: Porous plates are commonly used in the external humidification devices employed in proton exchange membrane fuel cells. In this study, the effect of a ribbed surface on the water transfer characteristics of a porous plate is investigated experimentally to elucidate the process by which heat and mass is transferred from a high-temperature, high-humidity gas (wet air) through porous media to a low-temperature, low-humidity gas (dry air). Experimental results show that a porous plate with ribs can promote the water transfer between the two gases and that the water transfer ability of the plate is markedly improved when the ribbed side is oriented toward the humidified gas.